Assessing Patient-Centred Outcomes in Lateral Elbow Tendinopathy: A Systematic Review and Standardised Comparison of English Language Clinical Rating Systems - Jonathan Peter Evans; Ian Porter; Jaheeda B. Gangannagaripalli; Charlotte Bramwell; Antoinette Davey; Chris D. Smith; Nicola Fine; Victoria A Goodwin; Jose M Valderas (SpringerOpen, 2019)
Abstract Background Lateral elbow tendinopathy (LET) is a common condition affecting adults. Although a lack of treatment consensus continues to prompt numerous effectiveness studies, there is a paucity of clear guidance on the choice of outcome measure. Our aim was to undertake a standardised evaluation of the available clinical rating systems that report patient-centred outcomes in LET. Methods A systematic review of studies reporting the development, assessment of metric properties and/or use of instruments aiming to quantify LET-specific patient-centred outcome measures was conducted in MEDLINE, Embase and CINAHL (inception-2017) adhering to PRISMA guidance. The evidence for each instrument was independently assessed by two reviewers using the standardised evaluating measures of patient-reported outcomes (EMPRO) method evaluating overall and attribute-specific instrument performance (metric properties and usability). EMPRO scores > 50/100 were considered indicative of high performance. Results Out of 7261 references, we identified 105 articles reporting on 15 instruments for EMPRO analysis. Median performance score was 41.6 (range 21.6-72.5), with four instruments meeting high-performance criteria: quick Disabilities of the Arm Shoulder and Hand score (qDASH) (72.5), DASH (66.9), Oxford Elbow Score (OES) (66.6) and Patient-Rated Tennis Elbow Evaluation (PRTEE) (57.0). One hundred seventy-nine articles reported instrument use internationally with DASH as the most frequent (29.7% articles) followed by PRTEE (25.6%), MEPS (15.1%) and qDASH (8.1%). The correlation between frequency of use and performance was r = 0.35 (95%CI − 0.11; 0.83). Conclusions This is the first study to provide standardised guidance on the choice of measures for LET. A large number of clinical rating systems are both available and being used for patients with LETs. Robust evidence is available for four measures, the DASH, QDASH, PRTEE and OES. The use of instruments in the literature is only in part explained by instrument performance.